الأزمة المالية في آسيا ومنعكساتها - محمود, يوسف (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يدرس البحث تجربة دول جنوب شرق آسيا, التي كانت تشكل أخم نموذج للتنمية في الدول النامية, وما هي أسباب انهيار هذه الدول, والانعكاسات المترتبة حول ذلك, خاصة وأن الأزمة في ظل العولمة الراهنة, ستلقي بظلالها على مختلف دول, واقتصاديات العالم . كما يدرس البحث السبل, والوسائل التي يمكن أن تلجأ إليها هذه الدول للخروج من الأزمة الراهنة, والنمو باقتصادياتها لتعود إلى مستويات النمو التي حققتها فيما مضى . ومن الناحية المنهجية, فقد وزع البحث على مجموعة من العناوين الفرعية, حيث بدأناه بمقدمة, بينا فيها لمحة موجزة حول تجربة دول آسيا, وأهميتها, وبعد ذلك انتقلنا لبيان أهمية, وأهداف البحث, ثم انتقلنا إلى عرض مادة البحث بخاتمة, تتضمن نظرة حول مستقبل تلك الدول . The research deals with the experience of the Asian Tigers countries which used to be considered the best example of development in the developing countries, as well as the reason behind the collapse of these countries and the consequences arised, specially that the crisis under the present prevailing inter globalization will be reflected on the various The research deals also with the methods and means which may be restored to by these countries for getting out the present crisis and for developing their economies in order to restore the development levels which achieved in the past . From the methodic standpoint ,the research was divided into a collection of subtitles, beginning with an introduction where we have stated a summary about the experience of the Asian Tigers countries and its important, then we moved to show the important aims of the research, afterwards we displayed the subject of the research ,ending with a close including a look about the future of these countries .